L-selectin gene polymorphism and its association with clinical mastitis, somatic cell score, and milk production in Polish Holstein-Friesian cattle - Magdalena Dusza; Joanna Pokorska; Joanna Makulska; Dominika Kulaj; Michal Cupial (Czech Journal of Animal Science, 2018)
Bovine mastitis is a widespread disease of the mammary gland, highly contributing to the increase in veterinary costs in dairy industry. In the present study, the genetic polymorphism within bovine L-selectin gene was analysed and its impact on clinical mastitis occurrence, somatic cell score (SCS), and milk production traits in Polish Holstein-Friesian cows was examined. Polymorphism within L-selectin gene, molecule responsible for neutrophil attachment to endothelium, might have a potential role in immune response to bacterial infections and udder health. Two hundred and six Polish Holstein-Friesian cows were genotyped by polymerase chain reaction-restriction fragment length polymorphism method. Two single nucleotide polymorphisms mutations within the coding sequence of L-selectin gene were identified (c.165G>A and c.567C>T). The effect of c.165G>A and c.567C>T mutations on SCS was highly significant (P = 0.0019 and P = 0.0003, respectively). Strong associations (P ≤ 0.0001) were also observed between L-selectin polymorphism and milk production traits (milk yield, milk fat percentage, and milk protein percentage). However, the polymorphism in the analysed gene had no influence on the resistance or susceptibility of cows to clinical mastitis (only the tendency toward significance, P = 0.06 for c.567C>T mutation was found). Potential exploitation of the information on the identified associations in genetic selection needs to confirm the obtained results in further investigations.